Flicker‐induced retinal vascular dilation in ipsi‐ and contralateral eyes of patients with carotid stenosis before and after carotid endarterectomy: a prospective study. Issue 7 (6th February 2022) - Ala‐Kauhaluoma, Marianne; Vikatmaa, Pirkka; Koskinen, Suvi M.; Ijäs, Petra; Nuotio, Krista; Silvennoinen, Heli; Relander, Kristiina; Lindsberg, Perttu J.; Soinne, Lauri; Summanen, Paula A.
Abstract: Purpose: Retinal vascular function was assessed in patients with carotid stenosis (CS) before and six months after carotid endarterectomy (CEA) and in controls at a six‐month interval. Methods: We studied 68 patients (81% male, mean age 69) and 41 healthy non‐medicated controls (77%, 68) from March 2015 to December 2018. Our ophthalmological examination included flicker‐induced arteriolar and venular measurements with a Dynamic Vessel Analyser in both eyes. Results: At baseline, flicker‐induced arteriolar and venular dilation was reduced in the ipsilateral eyes of the patients compared with dilation in the controls (arteriolar 1.0% versus 2.6%, p = 0.001 and venular 2.2% versus 2.8%, p = 0.049). These differences subsided after CEA. In patients' ipsilateral eyes, flicker‐induced arteriolar dilation was borderline postoperatively (preoperative 1.0% versus postoperative 1.6%, p = 0.06), whereas venular dilation increased (2.2% versus 2.8%, p = 0.025). We found various tentative associations with the change in flicker‐induced dilations after CEA, but not with the preoperative dilations. Conclusions: Postoperative recovery of the reduced flicker‐induced arteriolar and venular dilatation in the ipsilateral eye shows that, after CEA, the activity‐dependent vascular reactivity of haemodynamically compromised retinal tissue can improve.